The computer procedures to analyse the parameters of the Auditory Brainstem Responses in advanced retrocochlear tumors of the auditory pathway - BOCHENEK, W.; HATLIŃSKI, J.; RANACHOWSKI, Z. (Archives of Acoustics, 1998)
This investigation was aimed at a computer- supported analysis of the Auditory Brainstem Responses (ABR) recorded in both ears of 8 patients with unilateral tumor of the retrocochlear extracanalicular auditory pathway. Applying the computer procedure designed for processing the averaged ABR waveforms, the latencies in the time domain of waves I, III, V were calculated and the ratio of the amplitudes of those waves in both ears of the same patient was evaluated and correlated with the surgically verified size of the tumor.